After the Big Bang? Obstacles to the Emergence of the Rule of Law in Post-Communist Societies - Hoff, Karla; Stiglitz, Joseph E. (World Bank, Washington, DC, 2014)
With the collapse of communism in Eastern Europe and the Soviet Union in 1989-91, many economic reformers supported "Big Bang" privatization-the rapid transfer of state-owned enterprises to private individuals. It was hoped that Big Bang privatization would create the conditions for a demand-led evolution of legal institutions. But there was no theory to explain how this process of institutional evolution, including a legal framework for the protection of investors, would occur and, in fact, it has not yet occurred in Russia, in other former Soviet Union countries, in the Czech Republic, and elsewhere. A central reason for that, according to many scholars, is the weakness of the political demand for the rule of law. To shed light on this puzzle, the authors consider a model where the conditions for the emergence of the rule of law might be interpreted as highly favorable. Individuals with control rights over privatized assets can collectively bring about the rule of law simply by voting for it. These individuals are concerned with the wealth they can obtain from the privatized assets, and have two alternative strategies: building value and stripping assets. Building value under the rule of law yields higher benefits to a majority than stripping assets under no rule of law. But uncertainty about when the rule of law will be established may lead some individuals to choose an economic strategy-stripping assets, including converting corporate assets to private use-that gives them an interest in postponing the establishment of the rule of law. And therefore in the succeeding period, the rule of law may again not be in place, and so again individuals may strip assets. If they do, some of them may again have an interest in postponing the establishment of the rule of law. And so a weak demand for the rule of law can persist. The contribution of the paper is to show that the view that once stripping has occurred, the strippers will say "enough" and by supporting the rule of law seek public protection of their gains, is flawed. By abstracting from the obvious problem that strippers who obtain great wealth can buy special favored treatment from the state, the model highlights two less obvious flaws in the optimistic view about the Big Bang: First, that the asset-strippers can remove the assets from exposure to further stealing, and in that case they do not care about public protection for their gains. And second, that the perceived justice of a system is important to gaining the cooperation of those involved in the process of producing the rule of law (judges, regulators, jurors, potential offenders). Accordingly, state protection of asset strippers may be infeasible, even under an ostensible rule of law. Knowing this, strippers will be less supportive of the rule of law. The model makes one further point: what is at issue is how fast the rule of law will emerge. The presumption of the Big Bang strategy was that the faster state property was turned over to private hands, the faster a true market economy, including the rule of law, would be established. The analysis shows that, even if eventually a rule of law is established, the Big Bang may put into play forces that delay the establishment of the rule of law. The tortoise once again may beat the hare! Finally, the authors analyze the impact of certain policies, such as the particular structure of privatization and monetary policy. Policies that enhance the returns to investment and wealth creation rather than asset stripping not only serve to strengthen the economy in the short run, but enhance political support for the rule of law and thus put it in a position for stronger long-term growth.